Digital Signal Processing:Radio Frequency Applications - Ab Hadi, Nik Azran; Salleh, Azahari; Hashim, Nik Mohd Zarifie; Mohd Saad, Norhashimah; Ja'afar, Abd Shukur; Nain, A. A. (IJARET, 2015)
Nowadays,radio frequency is commonly use in many field of work and equipment.In this paper,the used of radio frequency actually very important to all and especially in communication field,is proposed.But there are some issue about radio frequency which is about the range and the frequency value.All this method that proposed here are from the source of frequency information and data about the common radio frequency.Value of frequency can be different and lot of value.Radio frequency is form when there are electromagnetic field is created.When this happened,it will propagate the frequency through the space.